Arsinothricin, an arsenic-containing non-proteinogenic amino acid analog of glutamate, is a broad-spectrum antibiotic - Nadar, Venkadesh Sarkarai (Commun Biol, 2019)
The emergence and spread of antimicrobial resistance highlights the urgent need for new antibiotics. Organoarsenicals have been used as antimicrobials since Paul Ehrlich’s salvarsan. Recently a soil bacterium was shown to produce the organoarsenical arsinothricin. We demonstrate that arsinothricin, a non-proteinogenic analog of glutamate that inhibits glutamine synthetase, is an effective broad-spectrum antibiotic against both Gram-positive and Gram-negative bacteria, suggesting that bacteria have evolved the ability to utilize the pervasive environmental toxic metalloid arsenic to produce a potent antimicrobial. With every new antibiotic, resistance inevitably arises. The arsN1 gene, widely distributed in bacterial arsenic resistance (ars) operons, selectively confers resistance to arsinothricin by acetylation of the α-amino group. Crystal structures of ArsN1 N-acetyltransferase, with or without arsinothricin, shed light on the mechanism of its substrate selectivity. These findings have the potential for development of a new class of organoarsenical antimicrobials and ArsN1 inhibitors.